Cytological organization of the alpha component of the anterior olfactory nucleus and olfactory limbus - Larriva-Sahd, Jorge A. (Frontiers in Neuroanatomy, 2012)
This study describes the microscopic organization of a wedge-shaped area at the intersection of the main and accessory olfactory bulbs, or olfactory limbus , and an additional component of the anterior olfactory nucleus or alpha accessory olfactory bulb that lies underneath of the accessory olfactory bulb. The olfactory limbus consists of a modified bulbar cortex bounded anteriorly by the main olfactory bulb and posteriorly by the accessory olfactory bulb. In Nissl-stained specimens the olfactory limbus differs from the main olfactory bulb by a progressive, antero-posterior decrease in thickness or absence of the external plexiform, mitral/tufted cell, and granule cell layers. On cytoarchitectual grounds the olfactory limbus is divided from rostral to caudal into three distinct components: a stripe of glomerular-free cortex or preolfactory area, a second or necklace glomerular area, and a wedge-shaped or interstitial area crowned by the so-called modified glomeruli that appear to belong to the anterior accessory olfactory bulb. The strategic location and interactions with the main and accessory olfactory bulbs, together with the previously noted functional and connectional evidence, suggest that the olfactory limbus may be related to both sensory modalities. The alpha component of the anterior olfactory nucleus, a slender cellular cluster (i.e., 650 x 150 µm) paralleling the base of the accessory olfactory bulb, contains two neuron types: a pyramidal-like neuron and an interneuron. Dendrites of pyramidal-like cells organize into a single bundle that ascends avoiding the accessory olfactory bulb to resolve in a trigone bounded by the edge of the olfactory limbus, the accessory olfactory bulb and the dorsal part of the anterior olfactory nucleus. Utrastructurally, the neuropil of the alpha component contains three types of synaptic terminals; one of them immunoreactive to the enzyme glutamate decarboxylase, isoform 67.